A degradação ambiental do Córrego Ribeirão Preto: uma proposta metodológica para o ensino de geografia no ensino médio - Santos, Heleno Ferreira dos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This research, conducted on the teaching of geography, aims to demonstrate the methodological construction of school -based environmental degradation river Ribeirao Preto, for students in the first grade of secondary school teaching Djanira Velho in Ribeirão Preto - SP, performed in the years 2012-2013. Initially, we sought to understand the role of geography, influenced by pedagogical trends based on neoliberalism, which address the development of individuals with skills and abilities. Subsequently, we seek theoretical frameworks that could base the present research, in opposition to the hegemonic pedagogies of learning to learn . We understand that the historical critical pedagogy, grounded in historical cultural psychology, based on studies of Vygotsky , corroborates to understand the concept of the subject and its relationship with teaching , revealing how the subject learns and internalizes the concepts produced historically , promoting development in minds of individuals . Through a dialogical action established with students from an approach focused on environmental issues, systematize the work in three steps: the first referred to the understanding of the object of study, the second, for the manufacture of the model and the third , the fieldwork . As steps were being met we reorganized activities focusing on questions of students. The activity, in this perspective, qualifies students and teachers in a dialectical relationship between subject and object of study. The analysis of students' productions made possible the search for a methodology that promotes interaction, focusing on understanding the stock. The instrumentalization of the subjects with the concepts of geography allowed them to make a qualitative reading of the place of experience , showing them the contradictions of urban space in the city of Ribeirão Preto , socially produced and individually appropriate, revealing the plot engendered by capitalist relations...

A presente pesquisa, realizada no campo do ensino da Geografia, tem como objetivo demonstrar a construção metodológica do ensino, baseada na degradação ambiental do córrego Ribeirão Preto, para os alunos da primeira série do Ensino Médio da escola Estadual Djanira Velho, em Ribeirão Preto – SP, realizada nos anos de 2012-2013. Inicialmente, procuramos entender o papel da Geografia, influenciada pelas correntes pedagógicas fundamentadas no neoliberalismo, que versam sobre o desenvolvimento dos indivíduos por competências e habilidades. Posteriormente, buscamos referenciais teóricos que pudessem embasar a presente pesquisa, contrapondo-se às pedagogias hegemônicas do ―aprender a aprender‖. Entendemos que a pedagogia histórico-crítica, fundamentada na psicologia histórico-cultural, pautada nos estudos de Vigostski, corrobora para entendermos a concepção de sujeito e sua relação com o ensino, revelando a maneira como o sujeito aprende e internaliza os conceitos produzidos historicamente, promovendo desenvolvimento na mente dos indivíduos. Por meio de uma ação dialógica estabelecida com os alunos, a partir de uma abordagem focada na questão ambiental, sistematizamos o trabalho em três etapas: a primeira referiu-se à compreensão do objeto de estudo, a segunda, à confecção da maquete e a terceira, ao trabalho de campo. À medida que as etapas foram sendo cumpridas, reorganizávamos as atividades com foco nas indagações dos alunos. A atividade, nessa perspectiva, qualifica alunos e professores numa relação dialética, entre sujeitos e o objeto de estudo. As análises das produções dos alunos possibilitavam a busca por uma metodologia que promovesse interação, focando a compreensão do manancial. A instrumentalização dos sujeitos com os conceitos da Geografia permitia-lhes fazer uma leitura qualitativa do lugar de vivência, mostrando-lhes as contradições do espaço urbano da cidade de Ribeirão Preto,...
Keywords: Geography - Study and teaching; Geografia - Estudo e ensino; Degradação ambiental; Ensino - Metodologia; Espaço urbano; Ribeirão Preto, Córrego (Ribeirão Preto, SP)